Use of technology in type 1 diabetes patients to improve health literacy: Literature review - Sabila, Misna Zakiyus; Fauziyyah, Jihan Nafisah; Istianah, Istianah; Septiani, Riswanti (Indonesian Journal of Health Science, 2025)
This study aims to examine the role of technology use in improving health literacy in patients with type 1 diabetes mellitus (T1DM). The research methodology was guided by the PRISMA guidelines. A comprehensive search was conducted in five major databases (PubMed, Scopus, Web of Science, CINAHL, ScienceDirect), using a combination of keywords related to T1DM, technology (e.g. mobile applications, telemedicine, Continuous Glucose Monitoring, artificial intelligence), and health literacy. Primary studies in English/Indonesian published between 2020 and 2024 were selected based on strict inclusion and exclusion criteria. Data were extracted, assessed for quality, and synthesized narratively-thematically. The 7 articles analyzed showed that various technologies, including web applications, simulation tools, serious games, and personal robots, were effective in improving knowledge, self-management skills, and self-confidence in patients with T1DM through access to real-time information and feedback. However, patient digital literacy was identified as a key facilitator and significant barrier to technology adoption and effectiveness. A patient-centered approach is also essential for successful implementation. Although AI (artificial intelligence) shows potential, the accuracy of general generative AI tools in specific medical information still requires validation and professional guidance. In conclusion, technology has great potential to improve health literacy in people with T1DM, but its optimization requires increased digital literacy and user-centered design. Further research is needed for large-scale validation and comprehensive integration of technology in T1DM care.